Human visual skills for brain-computer interface use: a tutorial. - Fried-Oken, Melanie; Kinsella, Michelle; Peters, Betts; Eddy, Brandon; Wojciechowski, Bruce (Disability & Rehabilitation: Assistive Technology, 2020)
Background and objectives: Many brain-computer interfaces (BCIs) for people with severe disabilities present stimuli in the visual modality with little consideration of the visual skills required for successful use. The primary objective of this tutorial is to present researchers and clinical professionals with basic information about the visual skills needed for functional use of visual BCIs, and to offer modifications that would render BCI technology more accessible for persons with vision impairments. Methods: First, we provide a background on BCIs that rely on a visual interface. We then describe the visual skills required for BCI technologies that are used for augmentative and alternative communication (AAC), as well as common eye conditions or impairments that can impact the user's performance. We summarize screening tools that can be administered by the non-eye care professional in a research or clinical setting, as well as the role of the eye care professional. Finally, we explore potential BCI design modifications to compensate for identified functional impairments. Information was generated from literature review and the clinical experience of vision experts. Results and conclusions: This in-depth description culminates in foundational information about visual skills and functional visual impairments that affect the design and use of visual interfaces for BCI technologies. The visual interface is a critical component of successful BCI systems. We can determine a BCI system for potential users with visual impairments and design BCI visual interfaces based on sound anatomical and physiological visual clinical science. As brain-computer interfaces (BCIs) become possible access methods for people with severe motor impairments, it is critical that clinicians have a basic knowledge of the visual skills necessary for use of visual BCI interfaces. Rehabilitation providers must have a knowledge of objectively gathering information regarding a potential BCI user's functional visual skills. Rehabilitation providers must understand how to modify BCI visual interfaces for the potential user with visual impairments. Rehabilitation scientists should understand the visual demands of BCIs as they develop and evaluate these new access methods.